2014
DOI: 10.1016/j.ejbt.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Application of microsatellite markers for breeding and genetic conservation of herds of Pantaneiro sheep

Abstract: Background:The aim of the present study was to assess the genetic diversity of Pantaneiro sheep, using microsatellite markers, in order to assist maintenance and management plans, enhance mating systems and reduce the inbreeding rate. A total of 127 animals were genotyped at eight microsatellite loci. They belonged to populations from the Experimental Farm of the Universidade Federal da Grande Dourados (UFGD) (Dourados/MS/Brazil) and Embrapa Pantanal (Corumbá/MS/Brazil). Results: The population of Pantaneiro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…Of the different types of molecular markers, STRs are suitable for studying genetic diversity because of their abundancethe large amount of allelic variation at each locus is highly polymorphic, their distribution throughout the genome is random, and inheritance is codominant (Rekha et al, 2016;Barcaccia et al, 2013;Putman et al, 2014). In addition, STRs are able to generate information for the planning of crossings and further selection of genotypes in genetic breeding programs (Faleiro et al, 2007;Crispim et al, 2014). The objective of the current research was to investigate 12 STR loci based on genetic diversity in sheep herds as well as the differentiation and relationship among the number of alleles and genetic links between Kazakh sheep breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Of the different types of molecular markers, STRs are suitable for studying genetic diversity because of their abundancethe large amount of allelic variation at each locus is highly polymorphic, their distribution throughout the genome is random, and inheritance is codominant (Rekha et al, 2016;Barcaccia et al, 2013;Putman et al, 2014). In addition, STRs are able to generate information for the planning of crossings and further selection of genotypes in genetic breeding programs (Faleiro et al, 2007;Crispim et al, 2014). The objective of the current research was to investigate 12 STR loci based on genetic diversity in sheep herds as well as the differentiation and relationship among the number of alleles and genetic links between Kazakh sheep breeds.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that average unbiased heterozygosity (Hz) of microsatellite markers studied in fat-rumped breeds, composite breeds, indigenous fat-tailed breeds, Karakul breeds and the wool breeds was 0.466, 0.555, 0.598, 0.659 and 0.662 respectively. Crispim et al (2014) reported that the population of Pantaneiro sheep from the UFGD exhibited a high average number of alleles (11.13) and allelic richness (10.66). The polymorphic information content was highly informative in the locus studied, resulting in a mean value of 0.71.…”
Section: Introductionmentioning
confidence: 99%
“…A total number of 100 alleles were estimated in the studies conducted on Pantaneiro sheep using eight microsatellite loci. The mean number of alleles per locus was 12.5 with a range of alleles from seven (SPS113) to 21 (OarCP49) (Crispim et al, 2014). Kunene et al (2014)…”
Section: Genetic Diversity Analysis Of Threementioning
confidence: 99%
“…The expected heterozygosity ranged from 0.5149 (MM12) to 0.8405 (MAF33). Crispim et al (2014) analysed Pantaneiro sheep and estimated the mean observed and expected heterozygosity values as 0.62 ± 0.13 and 0.71 ± 0.09, respectively. Kunene et al (2014) reported that the mean values for observed (H o ) and expected (H e ) heterozygosity were 0.57 and 0.61, respectively in studies conducted on four populations of Nguni (Zulu) sheep.…”
Section: Genetic Variation Studies On Barki Ossimi and Rahmani Sheepmentioning
confidence: 99%